Prácticas de Comunicación Alternativa de las Organizaciones Indígenas de Chimborazo, periodo 1980-2000. - Chiriboga Sinchiguano, Gissela Estefanía (2023)
This research paper addresses aspects of alternative communication practices applied in indigenous organizations of Chimborazo, one of the main provinces whit the largest number of indigenous inhabitants, themselves carry out different traditional activities that constitute alternative communication practices and which have been executed since ancient times, although unfortunately they have been ignored by various sectors of the rest of the Ecuadorian population and that has caused the scarce diffusion and ignorance of these ways of communication and relationship. Starting from the exposed, this research seeks to identify the alternative communication practices applied within the indigenous population of Chimborazo, from their reality and of living, this research is based on the use of qualitative methodology and through observation techniques and interviews with experts in the communicative field and connoisseurs of the indigenous population. Three communicative activities of the sector were analyzed, which were the Mingas, Assemblies and Festivals, determining that there is no individuality in these practices, since together they come to find solutions, help and even the enjoyment of sharing what they have and what they live, in all these community activities, person-to-person communication is the link to transmit information being scarce communication through technology, it must be added that each action they perform and symbology, it has a meaning and expresses a message as is the case of colors, clothing, food among others.